Electrophysiological characterization of entopeduncular nucleus neurons in anesthetized and freely moving rats - Benhamou, Liora; Cohen, Dana (Frontiers in Systems Neuroscience, 2014)
The EntoPeduncular nucleus (EP), which is homologous to the internal segment of the Globus Pallidus (GPi) in primates, is one of the two basal ganglia output nuclei. Despite their importance in cortico-basal ganglia information processing, EP neurons have rarely been investigated in rats and there is no available electrophysiological characterization of EP neurons in vivo. We recorded and analyzed the activity of EP neurons in freely moving as well as anesthetized rats, and compared their activity patterns. Examination of neuronal firing statistics during wakefulness suggested that similar to neurons recorded in the primate GPi, EP neurons are a single population characterized by Poisson-like firing. Under isoflurane anesthesia the firing rate of EP neurons decreased substantially and their coefficient of variation and relative duration of quiescence periods increased. Investigation of the relationship between firing rate and depth of anesthesia revealed two distinct neuronal groups: one that decreased its firing rate with the increase in anesthesia level, and a second group where the firing rate was independent of anesthesia level. Post-hoc examination of the firing properties of the two groups showed that they were statistically distinct. These results may thus help reconcile in-vitro studies in rats and primates which have reported two distinct neuronal populations, and in-vivo studies in behaving primates indicating one homogeneous population. Our data support the existence of two distinct neuronal populations in the rat EP that can be distinguished by their characteristic firing response to anesthesia.